Fourier‐based Registration for Robust Forward‐looking Sonar Mosaicing in Low‐visibility Underwater Environments. Issue 1 (9th April 2014) - Hurtós, Natàlia; Ribas, David; Cufí, Xavier; Petillot, Yvan; Salvi, Joaquim; Peynot, Thierry; Monteiro, Sildomar; Kelly, Alonzo; Devy, Michel
<x xml:space="preserve">Abstract</x> Vehicle operations in underwater environments are often compromised by poor visibility conditions. For instance, the perception range of optical devices is heavily constrained in turbid waters, thus complicating navigation and mapping tasks in environments such as harbors, bays, or rivers. A new generation of high‐definition forward‐looking sonars providing acoustic imagery at high frame rates has recently emerged as a promising alternative for working under these challenging conditions. However, the characteristics of the sonar data introduce difficulties in image registration, a key step in mosaicing and motion estimation applications. In this work, we propose the use of a Fourier‐based registration technique capable of handling the low resolution, noise, and artifacts associated with sonar image formation. When compared to a state‐of‐the art region‐based technique, our approach shows superior performance in the alignment of both consecutive and nonconsecutive views as well as higher robustness in featureless environments. The method is used to compute pose constraints between sonar frames that, integrated inside a global alignment framework, enable the rendering of consistent acoustic mosaics with high detail and increased resolution. An extensive experimental section is reported showing results in relevant field applications, such as ship hull inspection and harbor mapping.